Pathology of marketing program of the Export Development Bank of Iran using three-ramification model - Moahammadreza Rahimi; Ali Salmasnia (مدیریت مهندسی و رایانش نرم)
On one hand the presence of Iran as an observer in the WTO, and on the other hand the development of private banks, encounter the Iranian banks with a much more competitive environment. Survive in such situations requires its own mechanism, tools and strategies. Among these tools, we can mention to a marketing plan to achieve a sustainable ompetitive advantage. In this research, three-ramification model including structural, environmental, and behavioral aspects is used for investigating the pathology of marketing program of Export Development Bank of Iran. In this regard, a questionnaire based on three-ramification model is provided that its validity and stability are evaluated using experts and Cronbach's alpha, respectively. The results show that none of the structural, environmental, and behavioral aspects are not in a suitable situation.